Low-energy separation technique on purification of unsaturated fatty acids of palm stearin using methanol crystallization method - Fatimatuzzahraa Mohd Fadzel,; Jumat Salimon,; Darfizzi Derawi, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper discussed the development of a low-energy and cost-effective separation technique of saturated fatty acids (SFAs) from Malaysian Palm Stearin to purify the unsaturation level of its fatty acids. Unsaturated fatty acids (UFAs) pose great benefits in nutritional value and also can be utilized as a raw material in various food or non-food applications. A methanol crystallization separation method was introduced by manipulating the storage temperature as well as the mixture ratio of palm stearin fatty acids (PSFAs) and methanol as a solvent. The separated compounds were characterized using Fourier-transform infrared (FTIR) spectroscopy, proton (1 H-NMR), and carbon (13C-NMR) spectroscopy analysis techniques. The fatty acids composition for both UFAs and SFAs were determined through gas chromatography (GC) analysis technique. The highest separation yield was about 98% (wt.), using a mixture of PSFA:methanol; 1:9 (w/v) at the temperature of -20 °C. This method was successfully separated and purified the UFAs by increasing the unsaturation level of fatty acids about 172% as the final iodine value was about 98 compared to the initial value was at 36. The low-energy methanol crystallization separation method is a cheaper method compared to the conventional high-energy fractional distillation process and positively to be up scaled at industrial level.